The Principles of Investment Law in the Management of Mineral and Coal Resources Within Communal Land - Marthen B. Salinding (Fakultas Hukum Universitas Hang Tuah, 2017)
The legal forms of land tenure by communal society, known as communal, are varies in Indonesia. Communal title has been considered as a juridical and common term, although each of communal societies actually has their own different technical term. Making communal land as an investment place of managing mineral and coal resources might bring some legal issues for communal society. The first issue related to less optimal implementation of the principles of investment law by both government and investors. It would impact on the emerging conflicts between communal society and investors. Second, the position of communal land loaded by given-period mining permit would turn into the state property after the period ended.